The alkaloids of Ophiorrhiza cf. ferruginea - Arbain, Dayar; Putra, Deddi Prima; Lajis, Nordin H.; Sargent, Melvyn V.; Skelton, Brian W.; White, Allan H. (CSIRO Publishing, 1993)
Extraction of the aerial parts of Ophiorrhiza cf. ferruginea (Rubiaceae) has yielded the tertiary indole alkaloids dihydrocycloakagerine (1), 3, 14-dihydrodecussine (mostuenine) (3) and tetrahydroakagerine (4), and the quaternary indole alkaloid isomalindine (5). The structures of dihydrocycloakagerine (1) and isomalindine (5) are confirmed by the X-ray method.